Cost–benefit analysis of the CoCare intervention to improve medical care in long-term care nursing homes: an analysis based on claims data - Boris A. Brühmann; Klaus Kaier; Rieka von der Warth; Erik Farin-Glattacker (The European Journal of Health Economics, 2022)
Background: Providing adequate medical care to nursing home residents is challenging. Transfers to emergency departments are frequent, although often avoidable. We conducted the complex CoCare intervention with the aim to optimize nursing staff–physician collaboration to reduce avoidable hospital admissions and ambulance transportations, thereby reducing costs. Methods This prospective, non-randomized study, based on German insurance data, includes residents in nursing homes. Health care cost from a payer perspective and cost–savings of such a complex intervention were investigated. The utilisation of services after implementation of the intervention was compared with services in previous quarters as well as services in the control group. To compensate for remaining differences in resident characteristics between intervention and control group, a propensity score was determined and adjusted for in the regression analyses. Results The study population included 1240 residents in the intervention and 7552 in the control group. Total costs of medical services utilisation were reduced by exteuro468.56 ( p 0.167em<0.167em0.001) per resident and quarter in the intervention group. Hospital stays were reduced by 0.08 ( p 0.167em=0.167em0.001) and patient transports by 0.19 ( p 0.167em=0.167em0.049). This led to 1.66 ( p 0.167em<0.167em0.001) avoided hospital days or exteuro621.37 ( p 0.167em<0.167em0.001) in costs–savings of inpatient services. More services were billed by general practitioners in the intervention group, which led to additional costs of exteuro97.89 ( p 0.167em<0.167em0.001). Conclusion The benefits of our intervention clearly exceed its costs. In the intervention group, avoided hospital admissions led to additional outpatient billing. This indicates that such a multifactorial intervention program can be cost-saving and improve medical care in long-term care homes.
Keywords: I10; H51; 610; Claims data; Cost analysis; Secondary data; Propensity score; Complex health intervention; Nursing home residents